The characterization of chromosome breaks in Drosophila melanogaster. - Falk, D.R.; Halladay, D.L. (Mutation Research, 1986)
In the previous paper of this series, a total of 446 mutations of the para gene were isolated following gamma- or X-irradiation. Of these, 180 were shown to be chromosome deficiencies. In this analysis we examine the molecular distribution of breakpoints in a subset of strains [38] which have an endpoint in the 14F-15A5 region. We find that although the breakpoints are distributed throughout the entire region, there is some regional specificity to the distribution of those endpoints.